An 8000-year multi-proxy peat-based palaeoclimate record from Newfoundland: Evidence of coherent changes in bog surface wetness and ocean circulation. (May 2018) - Blundell, Antony; Hughes, Paul DM; Chambers, Frank M
Energy carried by warm tropical water, transported via the Atlantic Meridional Overturning Circulation (AMOC), plays a vital role in regulating the climate of regions bordering the North Atlantic Ocean. Previous phases of elevated freshwater input to areas of North Atlantic Deep Water (NADW) production in the early to mid-Holocene have been linked with slow-downs in the AMOC and changes in regional climate. Newfoundland's proximity in the North Atlantic region to the confluence of the Gulf Stream and the Labrador Current and to an area of NADW production in the Labrador Sea makes it an ideal testing ground to investigate the influence of past fluctuations in ocean circulation on terrestrial ecosystems. We use multi-proxy peat-based records from the east coast of Newfoundland to derive a proxy-climate signal for the past 8000 years, which we have compared with changes in ocean circulation. Prominent shifts towards near-surface bog water-table levels, reflecting cooler/wetter climatic conditions, are evident in the early mid-Holocene at c. 7830, 7500, 7220 and 6600 cal. BP with minor changes occurring at c. 6340 and 6110 cal. BP. These events are coherent with evidence of meltwater injections into the N. Atlantic and of reduced NADW production. More recent increases in bog surface wetness in the mid- to late Holocene at c. 4290 and c. 2610 cal. BP are also consistent with reported periods of reduced NADW production. Coherence between the bog-derived palaeoclimate record developed from Newfoundland and evidence of fluctuations in ocean current strength is apparent in the early mid-Holocene.